Host specificity and basic ecology of Mammomonogamus (Nematoda, Syngamidae) from lowland gorillas and forest elephants in Central African Republic - Červená, Barbora; Vallo, Peter; Pafčo, Barbora; Jirků, Kateřina; Jirků, Miloslav; Petrželková, Klára Judita; Todd, Angelique; Turkalo, Andrea K; Modrý, David (Parasitology, 2017)
Syngamid strongylids of the genus Mammomonogamus undoubtedly belong among the least known nematodes with apparent zoonotic potential and the real diversity of the genus remains hard to evaluate without extensive molecular data. Eggs of Mammomonogamus sp. are frequently found in feces of African forest elephants (Loxodonta cyclotis) and western lowland gorillas (Gorilla gorilla gorilla) in Dzanga-Sangha Protected Areas. Using sedimentation-based coproscopic techniques, we found the eggs of Mammomonogamus in 19·7% elephant and 54·1% gorilla fecal samples with 8-55 and 1-24 eggs per gram of fecal sediment for elephants and gorillas, respectively. We used a combination of light microscopy, scanning electron microscopy and analysis of cytochrome c oxidase subunit I (cox1) and a partial sequence of 18S rDNA isolated from single eggs to test the hypothesis of possible Mammomonogamus conspecificity in gorillas and elephants. Whereas 18S rDNA sequences were identical in both gorillas and elephants, we distinguished seven different haplotypes within the cox1. Two haplotypes were found in both gorillas and elephants suggesting sharing of Mammomonogamus. Assignment of the parasite to M. loxodontis is proposed. Provided sequences represent the first genomic data on Mammomonogamus spp.
Keywords: Strongyloidea; Sequence Analysis, DNA; Strongylida Infections; Prevalence; cox1; Dzanga-Sangha Protected Areas; Electron Transport Complex IV; infekce hlísticemi řádu Strongylida; Elephants; Central African Republic; proteiny červů; 18S rDNA; interspecies transmission; mužské pohlaví; prevalence; nemoci lidoopů; DNA, Helminth; Gorilla gorilla gorilla; RNA ribozomální 18S; Ape Diseases; Helminth Proteins; ženské pohlaví; zvířata; Host Specificity; DNA helmintů; fylogeneze; RNA, Ribosomal, 18S; Host-Parasite Interactions; Středoafrická republika; sekvenční analýza DNA; Gorilla gorilla; interakce hostitele a parazita; Loxodonta cyclotis; sloni; haplotype; Female; Phylogeny; hostitelská specificita; respirační komplex IV; Male; Animals